Influence of the pH on the corrosion protection of epoxy-silica-zirconia sol-gel coatings applied on EN AW-6063 aluminium alloy - Fontinha, I. R. (2013)
Aluminium alloys of 6000 series are particularly suited for the building industry due to their good corrosion resistance. However, they can suffer severe corrosion in acidic (polluted) and/or marine environments [1] and in contact with alkaline media like fresh cementitious materials. Therefore, architectural aluminium components are often coated to increase durability and aesthetical appearance, what requires its surface pre-treatment, traditionally Cr(VI) based, now facing severe restrictions. Within building industry, several “green” alternative treatments are already being applied, but they lack the anticorrosive action of the Cr(VI) compounds [2]. Another alternative under development, includes sol-gel silane based coatings, in particular, the organic-inorganic hybrid (OIH) ones, since they not only promote adherence, but also provide corrosion protection by barrier effect and in addition can incorporate corrosion inhibitors in their structure [3]. In this work, sol-gel coatings with in situ produced zirconia nanoparticles were synthesized from glycidoxypropyltrimethoxysilane (GPTMS) and zirconium n-propoxide (TPOZ) precursors by the sol-gel process and applied on EN AW-6063 alloy. Cerium nitrate was added to TPOZ sol during synthesis to be incorporated in the nanoparticles and act as corrosion inhibitor. Then cerium doped and undoped OIH coated aluminium alloy specimens were exposed to neutral, acidic (pH~3) and alkaline (pH~10) chloride solutions to assess coating chemical stability and anticorrosive properties in those media, since aluminium architectural coatings are usually required to be resistant both to acids and alkalis. The corrosion behaviour was evaluated by EIS (electrochemical impedance spectroscopy) and surface was characterized by SEM/EDS analyses.